2010
DOI: 10.1007/s11055-010-9301-9
|View full text |Cite
|
Sign up to set email alerts
|

Speech Disorders in Right-Hemisphere Stroke

Abstract: Clinical practice shows that right-hemisphere cerebral strokes are often accompanied by one speech disorder or another. The aim of the present work was to analyze published data addressing speech disorders in right-sided strokes. Questions of the lateralization of speech functions are discussed, with particular reference to the role of the right hemisphere in speech activity and the structure of speech pathology in right-hemisphere foci. Clinical variants of speech disorders, such as aphasia, dysprosody, dysar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Our results are not consistent with this interpretation, as we found no evidence of an asymmetrical CBT in our group of adults. In contrast, our findings of highly variable functional lateralization for DDK are in agreement with other reports of acute dysarthria following right hemisphere infarcts (one case/six in Kim et al 2003;10% of patients in Urban et al 2006; less than a third in Kumral et al 2007; see Dyukova et al 2010 for a review). An early study by Urban and colleagues (Urban et al 1997) for instance had reported on 18 patients with mild to moderate dysarthria, six of whom had suffered a right hemisphere infarct.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are not consistent with this interpretation, as we found no evidence of an asymmetrical CBT in our group of adults. In contrast, our findings of highly variable functional lateralization for DDK are in agreement with other reports of acute dysarthria following right hemisphere infarcts (one case/six in Kim et al 2003;10% of patients in Urban et al 2006; less than a third in Kumral et al 2007; see Dyukova et al 2010 for a review). An early study by Urban and colleagues (Urban et al 1997) for instance had reported on 18 patients with mild to moderate dysarthria, six of whom had suffered a right hemisphere infarct.…”
Section: Discussionsupporting
confidence: 93%
“…Disinhibited speech behaviors in, both deep and superficial lesions, display less precise specificity than the cortical structures. In analyzing published literatures on speech disorders of right hemispheric stroke in terms of locations, speech disorder types and possible mechanisms, poor understanding of mechanisms for the subcortical CA was pointed out and also that there is no single theory providing a complete explanation of the speech dysfunction in CA (17). …”
Section: Discussionmentioning
confidence: 99%
“…A stroke in the right cerebral hemisphere causes one or more types of language impairment (Dyukova, Glozman, Titova, Kriushev, & Gamaleya, 2010). Several studies have used various approaches to determine the role of the right hemisphere in language function.…”
mentioning
confidence: 99%